Sustainability, growth, and poverty alleviation: a policy and agroecological perspective - Vosti, Stephen A.; Reardon, Thomas (International Food Policy Research Institute, 1997)
Developing countries are under pressure to produce more food for their growing populations, conserve natural resources, and reduce poverty. In the short term, however, these goals may compete with one another. This book focuses on the interactions between agricultural growth and environment and between environment and poverty. The chapters analyze and illustrate these interactions with case study evidence from the developing world in general and from specific agroclimatic zones in Africa, Asia, and Latin America. The contributors also discuss what these links mean for development policies, agricultural technologies, and social and economic institutions. With a clearer picture of how these goals interact, policymakers and researchers can design strategies for working more effectively to meet them.